Distributed asynchronous algorithms with stochastic delays for constrained optimization problems with conditions of time drift - Beidas, Bassem F.; Papavassilopoulos, George P. (Parallel computing, 1995)
A distributed asynchronous algorithm for minimizing a function with a nonstationary minimum over a constraint set is considered. The communication delays among the processors are assumed to be stochastic with Markovian character. Conditions which guarantee the mean square and almost sure convergence to the sought solution are presented. We also present an optimal routing application for a network that connects various U.S. cities. Results of the extensive simulation that we implemented assert the practical applicability of distributed asynchronous algorithms with stochastic delays. Comparison results for varying the probability distribution of these delays are provided. The impact of varying the communication delay bound and the stepsize is also assessed.